THE THERMOLUMINESCENCE (TL) DOSE RESPONSE OF COMPOSITE PEAK 5 IN LIF:MG, TI (TLD-100): DEPENDENCE ON THE ORDER OF KINETICS. Issue 6 (28th February 2023) - Nemirovsky, Dimitry; Oster, Leonid; Reshes, Galina; Biderman, Shlomo; Bokobza, Yogev; Sterenberg, Matan; Eliyahu, Ilan; Shapiro, Alexander; Herman, Benny; Horowitz, Yigal
Abstract: A seeming contradiction in the prediction of the spatially correlated trapping center/luminescent center model applied to LiF:Mg, Ti has been the linear/supralinear behavior of the dose response of glow peak 5a. In the TC/LC model, the localised electron–hole recombination, giving rise to glow peak 5a, is expected to result in an extended region of linear dose response. Deconvolution of the glow curves based on first order kinetic peak shapes results, however, in a dose response of peak 5a, which closely resembles the linear/supralinear dose response of peak 5. It is demonstrated herein that when general-order kinetics peak shapes are used for peak 5a, the analysis can result in a linear dose response of glow peak 5a up to dose levels as high as 30 Gy, well beyond the 1-Gy onset of supralinearity of peak 5. The extended linearity suggests a resolution of the contradiction.